Sistem Informasi Pelacak Kendaraan - Sofyan Mufti Prasetiyo; Baresi Bahtiar; Dwi Noor Saputra; Muhamad Febriyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Nowadays, smart communication devices (smartphones and Android) are in great demand by many people. In addition to being easy to operate, smartphones can also be used for monitoring, locating, etc. During these times the vehicle is not under the supervision of the vehicle owner, so it is very vulnerable to a decrease in the vehicle being taken away by the lessee. Therefore we need a system that can track the position of the vehicle. When the vehicle is lost, the vehicle can already know its position and whereabouts and immediately takes action. The system to be built is a vehicle position tracking application using Android-based GPS and GSM technology. This application uses the Java programming language and has features such as dashboard pages, maps, search. , and account information. In addition, this application is also connected to Google Maps and it is hoped that the vehicle tracking information system will know the position of the vehicle in real time.